Pemidanaan Sebagai Ultimum Remidium Dalam Memberikan Perlindungan Hukum Terhadap Hak-Hak Konsumen Pada Suatu Transaksi Elektronik - Indrawan, Ronny (Esensi Hukum, 2019)
This paper discusses the issue concerning the legal protection of consumer rights in transaction activity which at present its development has started to use technology based on computer and telecommunication in cyberspace. This paper argues that in today's era there are often problems related to electronic transactions, especially with regard to consumer rights. Therefore, in providing legal protection against the fulfillment of consumer rights, the study from the perspective of criminal law becomes very important. Furthermore, this paper explains, among other things, the rights of consumers to be protected by criminal law, criminal forms in electronic transactions, the modus operandi of criminals, and applicable criminal sanctions for the perpetrators.